“Toma cuidado com esses baianos”: migração, identidade e preconceito na relação entre estabelecidos e outsiders em Inhumas (GO) - Oliveira, Túlio Fernando Mendanha de (2017)
This paper seeks to ascertain through the anthropological and sociological bias of the power relations of Norbert Elias and John L. Scotson in The Established and the Outsiders (2000) the relationships that exist between prejudice and identity, and the differentiation between Northeastern migrants and the population of City of Inhumas-GO. At first, I seek to investigate how the city of Inhumas has the migration / immigration intrinsically linked to its construction and consolidation. In the next chapter, supported by the historical construction of the city, we try to understand, through ethnography and oral history narrated by older residents, how these residents identify themselves, as well as the way in which they construct their memory. Finally, I intend to establish a discussion related to the identity and difference between both groups, through interviews conducted with migrants from various regions of the Northeast and residents of Inhumas. It is noteworthy that there is a certain search for differentiation between the so-called goianos or belonging to a possible goiano‟s identity, of the Northeastern migrants, while the local inhabitants are seen as established, the outsiders‟ notions are delegated to the migrants, which makes them to be adjectived with pejorative and prejudiced notions.